Factors associated with usage of oral rehydration salts for diarrheal treatment among children under 5 years old in Selatan Balikpapan, Indonesia - Tugiman, Tri Murti (2016)
Diarrheal disease is one of the leading causes for death among children under 5 years old. Oral Rehydration Salts (ORS) have contributed to a substantial reduction in death among infants due to diarrhea. The levels and the factors affecting the usage of ORS had been unknown in Balikpapan Selatan, Indonesia. A cross-sectional study was to determine the usage of ORS in the treatment of diarrhea among children under 5 years old and its associated factors mothers attending health clinics and study become important consideration for health workers in developing program to increase mothers awareness practice diarrhea treatment. The study was conducted at health clinics in Balikpapan Selatan Indonesia. Stratified random sampling was employed to select the respondents among the mothers attending health clinics. The data were collected from 1st May 2012 to 1st August 2012 (3 months). All respondents were interviewed face-to-face using pre-tested questionnaire. The questionnaire consisted of demographic information, knowledge about diarrhea, belief, perception, health service factors, and costs factors. As for analysis of data, chi-square test and logistic regression analysis in SPSS 22.0 were used, whereas the level of significance for all statistics was set at p<0.05. The response rate for this study was 90%. Significant associations had been discovered between usage of ORS and age of children (P=0.002), birth order (P<0.001), current marital status (P=0.026), highest education level (P=0.013), occupation (P=0.001), knowledge on diarrhea (P=0.008), belief among mothers (P<0.001), perception of mothers (P<0.001), as well as health service factors (P<0.001). The logistic regression analysis revealed that the factors associated with usage of ORS were age of mothers (Adj, OR=4.657; 95% CI: 1.42, 15.26); marital status (Adj, OR=16.55; 95%CI:4.21, 65.06); level of education (Adj, OR=3.017; 95%CI: 1.26, 9.18); occupation (Adj, OR=3.399; 95%CI: 1.26, 9.18); knowledge on diarrhea among mothers (Adj, OR=33.23; 95%CI: 13.56, 81.45); belief among mothers (Adj, OR=16.00 %CI: 5.27, 48.63); as well as perception of mothers (Adj, OR=19.12%; 95%CI: 2.67, 136.83). In conclusion, factors related to mothers, such as age, marital status, level of education, occupation, knowledge, belief, perception, and health service factors, as well as sources and modes of obtaining ORS had been found the usage of ORS solution among children under 5 years old suffering from diarrhea in Balikpapan Selatan Indonesia.